Yield Response, Nutritional Quality and Water Productivity of Tomato (Solanum lycopersicum L.) are Influenced by Drip Irrigation and Straw Mulch in the Coastal Saline Ecosystem of Ganges Delta, India - Samui, Indranil; Skalicky, Milan; Sarkar, Sukamal; Brahmachari, Koushik; Sau, Sayan; Ray, Krishnendu; Hossain, Akbar; Ghosh, Argha; Nanda, Manoj Kumar; Bell, Richard W.; Mainuddin, Mohammed; Brestic, Marian; et al. (Sustainability, 2020)
In the coastal zone of the Ganges Delta, water shortages due to soil salinity limit the yield of dry season crops. To alleviate water shortage as a consequence of salinity stress in the coastal saline ecosystem, the effect of different water-saving (WS) and water-conserving options was assessed on growth, yield and water use of tomato; two field experiments were carried out at Gosaba, West Bengal, India in consecutive seasons during the winter of 2016–17 and 2017–18. The experiment was laid out in a randomized block design with five treatments viz., surface irrigation, surface irrigation + straw mulching, drip irrigation at 100% reference evapotranspiration (ET0), drip irrigation at 80% ET0, drip irrigation at 80% ET0 + straw mulching. Application of drip irrigation at 80% ET0 + straw mulching brought about significantly the highest fruit as well as the marketable yield of tomato (Solanum lycopersicum L.). The soil reaction (pH), post-harvest organic carbon, nitrogen, phosphorus and potassium (N, P and K) status and soil microbial population along with the biochemical quality parameters of tomato (juice pH, ascorbic acid, total soluble solids and sugar content of fruits) were significantly influenced by combined application of drip irrigation and straw mulching. Surface irrigation significantly increased the salinity level in surface and sub-surface soil layers while the least salinity development was observed in surface mulched plots receiving irrigation water through drip irrigation. The highest water productivity was also improved from drip irrigation at 80% ET0 + straw mulched plots irrespective of the year of experimentation. Such intervention also helped in reducing salinity stress for the tomato crop. Thus, straw mulching along with drip irrigation at 80% ET0 can be recommended as the most suitable irrigation option for tomato crop in the study area as well as coastal saline regions of South Asia. Finally, it can be concluded that the judicious application of irrigation water not only increased growth, yield and quality tomatoes but also minimized the negative impact of soil salinity on tomatoes grown in the coastal saline ecosystem of Ganges Delta.